STRATEGI TAHFIDZ DALAM MEMBIASAKAN KETERTIBAN ANAK KELOMPOK B TK ISLAM DUTA ANANDA SLEMAN - Trisna, Dewi Sri Hening; Noor Muhammad, Azamul Fadhly; Cholimah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes how Tahfidz Al-Qur'an strategies shape orderly-character habituation among Group B kindergarten children, a foundation crucial for later formal-education readiness. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving tahfidz teachers, the principal, and parents. Results show that a structured daily routine, namely muraja'ah, listening to examples, collective repetition, and individual memorization submission, significantly transformed children's behavior. The resulting orderly character spans physical posture (sitting properly), self-regulation (focus and emotional control), and compliance with social rules such as queuing and waiting for turns, with effects extending into the home environment. Teachers' direct role modeling emerged as the primary supporting factor for the program's success. The study concludes that integrating religious values through consistent habituation strategies effectively builds early childhood behavioral control.